Effect of Harvesting Moisture Content on Development of Fissures and Head Rice Recovery in Basmati Paddy - Gupta, Ravi; Kashyap, M C; Garg, M K; Yadvika, Yadvika (Journal of Agricultural Engineering, 2002)
Three moisture contents at the time of harvesting were 20%, 18% and 16% (w.b.) for Taraori Basmati and 22%, 20% and 18% (w.b.) for Basmati-370. The milling moisture content was 13.0±0.5 percent (w.b.) and degree of polish was 5-6 percent for all the samples. Basmati-370 was less prone to cracking than Taraori Basmati and could bear more internal stresses. White head rice yield of Basmati-370 variety was more as compared to the Taraori Basmati variety. The value of white head rice yield (WHRY) observed were 57.4% for Basmati-370 and 50.49% for Taraori Basmati when harvesting was done at 20% w.b. and this reduced to 54% for Basmati-370 and 45% for Taraori Basmati at 16% (w.b.).